Hafnium in nuclear power industry: the evolution of increasing of the economic indicators and the operation safety of pressurized water nuclear reactors - Shilyaev, B.A.; Ulybkin, A.L.; Kovtun, K.V.; Rybka, A.V.; Kutny, V.E.; Pudov, A.O. (Вопросы атомной науки и техники, 2018)
А further increase of the reliability, safety and efficiency of nuclear reactors, the extension of the nuclear fuel campaign and a better control of the fuel burning-out level demand to search for and use new materials. New materials are also necessary for new energy release management elements in the active zone. In this paper, the potential place that hafnium could occupy in the solution of the mentioned tasks is discussed. The high values of the absorption cross-section for thermal and epithermal neutrons, high corrosion resistance, good mechanical properties and heat conduction of hafnium allow for its use, without any barrier coatings, as the absorbing and structural material for regulation rods of nuclear reactors. Another application of high purity hafnium in the nuclear power industry can be in the emitter material of Compton-type Self-Powered Neutron Detectors (SPND). Such SPND will have instant response to neutron flux changes, which will allow to reach positive effects on the reactor safety and efficiency: increase fuel burning-out times; control the crisis boiling coordinates and time; exclude the processes, which could cause heavy accidents). Збільшення надійності та безпеки, підвищення ефективності ядерних реакторів, подовження кампанії палива та контроль рівня його вигоряння вимагають пошуку і використання нових матеріалів, в тому числі, й для елементів управління енерговиділенням в активній зоні. У роботі розглядається, яке місце може зайняти гафній при вирішенні перерахованих завдань. Високі перетини поглинання теплових і резонансних нейтронів, корозійна стійкість, механічні властивості та теплопровідність гафнію дозволяють використовувати його без оболонок і покриттів в якості поглинаючого та одночасно конструкційного матеріалу для регулюючих стрижнів ядерних реакторів. Іншим застосуванням чистого гафнію в ядерній енергетиці може бути використання його в якості емітера в комптонівському детекторі прямого заряду (ДПЗ). Такий ДПЗ буде мати миттєву реакцію на зміни потоку нейтронів, що багато в чому дозволить досягти позитивних ефектів (збільшення вигоряння палива; контролю координати і часу кризового кипіння; виключення процесів, що призводять до тяжких аварій). Увеличение надёжности и безопасности, повышение эффективности ядерных реакторов, продление кампании топлива и контроль уровня его выгорания требуют поиска и использования новых материалов, в том числе и для элементов управления энерговыделением в активной зоне. В работе обсуждается, какое место может занять гафний при решении перечисленных задач. Высокие сечения поглощения тепловых и резонансных нейтронов, коррозионная стойкость, механические свойства и теплопроводность гафния позволяют использовать его без оболочек и покрытий в качестве поглощающего и одновременно конструкционного материала для регулирующих стержней ядерных реакторов. Другим применением чистого гафния в ядерной энергетике может быть использование его в качестве эмиттера в комптоновском детекторе прямого заряда (ДПЗ). Такой ДПЗ будет обладать мгновенной реакцией на изменения потока нейтронов, что во многом позволит достичь положительных эффектов (увеличения выгорания топлива; контроля координаты и времени кризисного кипения; исключения процессов, приводящих к тяжелым авариям).